1996
DOI: 10.1016/0920-5632(95)00632-x
|View full text |Cite
|
Sign up to set email alerts
|

Topological σ-models and the large-N matrix integrals

Tohru Eguchi

Abstract: In this paper we describe in some detail the representation of the topological CP 1 model in terms of a matrix integral which we have introduced in a previous article. We first discuss the integrable structure of the CP 1 model and show that it is governed by an extension of the 1-dimensional Toda hierarchy. We then introduce a matrix model which reproduces the sum over holomorphic maps from arbitrary Riemann surfaces onto CP 1 . We compute intersection numbers on the moduli space of curves using geometrical m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…where the Q (n) are the charges defined by (28) and the F (n) are the corresponding fluxes with respect to the t 1 flow, Explicitly Calculations of this type were first performed (for N = 2 and small values of n) in [15,16] and then (for N = 3 and small values of n) in [17].…”
Section: Lemma 72mentioning
confidence: 99%
See 1 more Smart Citation
“…where the Q (n) are the charges defined by (28) and the F (n) are the corresponding fluxes with respect to the t 1 flow, Explicitly Calculations of this type were first performed (for N = 2 and small values of n) in [15,16] and then (for N = 3 and small values of n) in [17].…”
Section: Lemma 72mentioning
confidence: 99%
“…Calculations of this type were first performed (for N = 2 and small values of n) in [15,16] and then (for N = 3 and small values of n) in [17].…”
mentioning
confidence: 99%
“…The Landau-Ginzburg model with the (twisted) superpotential W , where W is as above, and its complex conjugate W has been considered by K. Hori and C. Vafa [18] (see also [13,5,7,16]). They showed that its correlation functions in the BPS sector are related to those of the twisted sigma model of P 1 , which is the sense in which the two theories are mirror dual to each other.…”
Section: Introductionmentioning
confidence: 99%